Research of Transformer Rubber Damper for High-speed Train - FENG Wan-sheng; CHENG Chang; CHENG Hai-tao; LUO Jun (机车电传动)
To suppress high-speed carbody suspension components vibration of transformers, convertor, accumulator and otherequipment, rubber shock absorber was designed to reduce equipment vibration. By combining of theory analysis and engineering service,vibration relationship between rubber damper and transformer and car body connection was analyzed, as well as stiffness and dampingproperties matching, and appropriate parameter for damper was designed to avoid vibration between transformer and car body.